(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
On the occasion of the Professional Days of Forester, Hydrologist and Meteorologist, at the initiative of the Faculty of Geography and Geology of YSU, with the financial support of the Committee on Higher Education and Science of the RA Ministry of Environment (Research Project No. 24WS-1E035), an international three-day conference entitled “Current Issues in Hydrometeorology and Environmental Monitoring in a Changing Climate: Adaptation, Sustainability and Production Process” was held from March 20 to 22, 2025. During the conference, the achievements and prospects of the development of fundamental and applied scientific research in the field of hydrometeorology, environmental monitoring, biodiversity and ensuring ecological safety were discussed and presented, the priority issues, development patterns and prospects in the field of hydrometeorology were identified and revealed, the problems of economic management of the development of modern society and legal regulation of the ecosystem were assessed, the role of the latter in solving the socio-economic problems of the region was assessed, the current state of the environment, and the issues of climate change were analyzed and assessed. 65 reports were made in offline and online formats, a significant part of which has great scientific value and great scientific-applied potential. In total, more than 200 participants (in person and online) participated in the conference, including state officials, representatives of international organizations, representatives of Armenian and foreign universities, and famous people. The conference was attended by renowned scientists from France, Germany, Russia, Uzbekistan, Belarus, and Tajikistan. The main achievements of this scientific event were the expansion of international cooperation and the exchange of experience. At the end of the conference, the speakers were awarded certificates and letters of appreciation.